Effect of triggering angles on the crushing mechanisms of hybrid woven kenaf/aluminum hollow cylinders - Ismail, Al Emran; Mat Noor, Fazimah; Mohamad, Zaleha; Madlan, Mohd Amran; Rahim, Mohammad Zulafif; Ibrahim, Mohd Rasidi; Ahmad, Sufizar; Abdol Rahman, Mohd Nasrull; Md Salleh, Salihatun; Sadikin, Azmahani; Mahzan, Shahruddin; Muhd Nor, Nik Hisyamudin (IOP Publishing, 2017)
This paper presents the effect of triggering angles constructed on the top of hybrid woven kenaf/aluminium hollow cylinders on the energy absorption performances. The crushing performances of aluminium tubes can be found widely in open literature. However, lack number of work on the hybridizing the aluminium tubes with woven kenaf fibre is found. Woven kenaf mats are produced and bathed with polymeric resin before they are wrapped around the aluminium tubes twice. Different fibre orientations, o are used where  = 0, 15, 30 and 45. Once the hybrid composite hardened, one of their end are chamfered using different angles of 0o, 30o, 45o and 60o. The tubes are quasi-statically compressed in order to obtain their force-displacement responses and crashworthiness parameters are extracted and discussed with the relation of fibre orientations and chamfering angles. It is found that the chamfering angles are only affected the force-displacement curves during the first stage of elastic deformation whereas there is no obvious effect in the second stage. However, varying the fibre orientations are slightly increased the force-displacement curves especially when the fibre is orientated with 30o. Based on the fracture mechanism observations, most of composite experienced large fragmentation indicating that the composites absorbed the crushing energy ineffectively